RDT performance through high-throughput bead-based antigen detection during malaria school survey in Senegal - Diallo, Mamadou Alpha; Ndiaye, Ibrahima M.; Sow, Djiby; Seck, Mame Cheikh; Diongue, Khadim; Touré, Mariama; Battle, Katerine E.; Ngom, Bassirou; Sy, Mouhamad; Gaye, Amy; Ndiaye, Yaye Dié; Garba, Mamane Nassirou; et al. (Frontiers in Parasitology, 2025)
BackgroundRapid Diagnostic Tests (RDTs) remain the frontline tool for malaria diagnosis, but their performance in detecting low-density infections is variable and poorly characterized at the population level.ObjectiveThis study aimed to evaluate the diagnostic performance of HRP2-based RDTs by integrating high-throughput bead-based HRP2 quantification into school-based malaria surveys.MethodsA cross-sectional study was conducted in three Senegalese districts (Diourbel, Tambacounda, and Kédougou), enrolling 3,748 school-aged children. All participants were tested using RDTs, and dried blood spots were analyzed with a multiplex bead-based HRP2 assay. A Gaussian mixture model was used to classify HRP2 positivity, and logistic regression assessed the relationship between HRP2 concentration and RDT outcome.ResultsThe overall RDT positivity rate was 7.2%, with marked heterogeneity across districts (Diourbel: 3.0%, Kédougou: 15.9%, Tambacounda: 7.6%). HRP2 concentration was the strongest predictor of RDT positivity (aOR: 14.55 per log10 increase, 95% CI: 11.14–19.00). RDT limits of detection (LOD95) varied significantly: 3.9 ng/mL in Tambacounda, 121.2 ng/mL in Kédougou, and 204.3 ng/mL in Diourbel.ConclusionRDTs remain a useful surveillance tool, particularly in moderate- to high-transmission settings. However, reduced sensitivity at lower antigen concentrations in hypo-endemic areas highlights the value of complementary high-sensitivity assays for elimination-focused strategies. Future research should explore the application of these integrated diagnostic approaches in regions without seasonal malaria chemoprophylaxis intervention.